The profile of hydrocarbons and heavy metals in surface sediments from Batang Ai hydroelectric Dam, Lubok Antu, Sarawak - Nur Aein, Binti Razali (Universiti Malaysia Sarawak, UNIMAS, 2012)
A study was carried out to determine distribution of hydrocarbons and heavy metals in fresh water surface sediments from Batang Ai hydroelectric Dam, Lubok Antu, Sarawak. The surficial sediments from seven sampling sites in the vicinity of Batang Ai hydroelectric Dam were analyzed for hydrocarbons (aliphatic and aromatic) using gas chromatography flame ionization detector (GC-FID) and also heavy metal using atomic absorption spectrophotometer (AAS). The total concentration aliphatic hydrocarbons varied from 804 – 1014.39 μg/g, while total concentration of PAH varied from 1248 - 7827 ng/g dry weights. Eleven heavy metals analyzed are Ni, Cu, Mn, Pb, Cd, Zn, Cr, Sn, Ag, As and Bi. Sediment from sampling site ST2 which is near to the outflow area were highly deposited with heavy metals compared to other sampling sites at Batang Ai hydroelectric Dam. The concentration level of chromium (Cr) and copper (Cu) from site ST2 can be classified as heavily polluted.